Supporting ad-hoc resource sharing on the Web: A peer-to-peer approach to hypermedia link services. - Zhou, J; Hall, W; Roure, D; Dialani, V (2007)
The key element to support ad-hoc resource sharing on the Web is to discover resources of interest. The hypermedia paradigm provides a way of overlaying a set of resources with additional information in the form of links to help people find other resources. However, existing hypermedia approaches primarily develop mechanisms to enable resource sharing in a fairly static, centralized way. Recent developments in distributed computing, on the other hand, introduced peer-to-peer (P2P) computing that is notable for employing distributed resources to perform a critical function in a more dynamic and ad-hoc scenario. We investigate the feasibility and potential benefits of bringing together the P2P paradigm with the concept of hypermedia link services to implement ad-hoc resource sharing on the Web. This is accomplished by utilizing a web-based Distributed Dynamic Link Service (DDLS) as a testbed and addressing the issues arising from the design, implementation, and enhancement of the service. Our experimental result reveals the behavior and performance of the semantics-based resource discovery in DDLS and demonstrates that the proposed enhancing technique for DDLS, topology reorganization, is appropriate and efficient. © 2007 ACM.